GNIFICADOS DE DOENÇA MENTAL EXPRESSOS EM REPRESENTAÇÕES GRÁFICAS DE INDIVÍDUOS PSICÓTICOS - Begnini, Danusa; Amthauer, Camila; Costa, Henrique M.; Sand, Isabel C. P. V. D.; Hildebrandt, Leila M.; Gasparini, Danieli (Salão do Conhecimento, 2013)
Resumo